SURVEY ON THE IMPLEMENTATION OF HEALTH EDUCATION BY NURSES IN THE INPATIENT ROOM OF TYPE B HOSPITAL - Jannah, Latifah Nur; Kurniawan, Dicky Endrian; Ardiana, Anisah; Handoko, Yudho Tri (Politeknik Medica Farma Husada Mataram, 2024)
A nurse is a professional who can provide care to individuals, families, groups, or communities, both in sickness and health. One of the important tasks of nurses is as educators. Health education is a form of education that aims to change the behavior of individuals, groups and communities so that they can improve their health independently. The purpose of this study was to analyze the implementation of the role of nurses as providers of health education to patients. This study used a descriptive survey design. The research sample used a total sampling technique of 18 respondents consisting of nurses who served in the inpatient room of a type B hospital. The measuring instrument used an instrument in the form of a Nurse's Education Patient Questionnaire (NEPQ). Data analysis using exploratory descriptive. The results obtained 67% of nurses in the good category on the values and knowledge of nurses, 50% in the good category on the environment for providing health education, 61% in the good category on the organization of health services, 61% in the good category on interdisciplinary and peer cooperation, 61% in the good category on activities providing health education. Supporting factors for nurses as educators include the existence of a PKRS team and clear documentation related to health education documentation. While the inhibiting factors include the lack of support from the room manager and the lack of availability of nurses' time. Nurses are expected to further improve the responsiveness dimension and hospital management to increase support or encouragement, especially holding socialization/workshops and encouraging health education providers by nurses to get training, routine scheduling, and supervision to optimize the provision of health education.